CONTROL OF ALCOHOLIC DRINKS' DISTRIBUTION IN SUPPORTING TOURISM BUSINESS - Abdul Rosid Novianto; Erlisa Akhlakul Karimah; Febe Alfreda Wijaya; Tyatara Wellnadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
In Surabaya, the demand for alcoholic drinks by tourists is quite high so that sales of alcoholic drinks support the running of tourism businesses such as hotels, bars, restaurants, pubs, night clubs and discotheques. Related to this case, the government made efforts to supervise and control the distribution of alcoholic drinks by making laws and regulations related to the control of the alcoholic drinks’ distribution and stipulating requirements for tourism places that sell alcoholic drinks, one of which must have special permits, especially TDUP and SIUP-MB. However, it is not uncommon for several parties to commit violations by running their business without having a permit according to the laws and regulations. For this reason, law enforcement needs to be carried out by law enforcement officials, which in this case includes administrative law enforcement. Administrative law enforcement is implemented in the form of supervision and application of administrative sanctions. Keywords: Alcoholic Drinks, Tourism Business, Control, Administrative Law Enforcement